Kandungan Fenol dan Aktivitas Antioksidan Makroalga Bentik Caulerpa racemosa (Forsskal) dari Teluk Hurun, Lampung - Joko Santoso; Diini Fitriani; Yusli Wardiatno (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Caulerpa racemosa is a green benthic macroalga that mainly grows in tropical regions which is expected to bask of strong ultraviolet radiation from sunlight. This circumstance can cause to increase levels of reactive radical species. To reduce and/or protect, organism like macroalga may change its metabolism and stimulate to produce some active compounds, therefore, tropical macroalgae are estimated possessing a large number of active compounds such as antioxidant. In this experiment, edible green benthic macroalga Caulerpa racemosa grown in different water condition were used. The content of total phenol and antioxidant activity of ethyl acetate extract were performed. Pearson correlation between waters condition and antioxidant activities i.e. total phenol and DPPH inhibition were also analyzed. Caulerpa racemosa grown in station 2, exposed in strong radiation from sunlight, had the highest content of total phenol and percentage of DPPH inhibition, with their values were 12.60% and 46.43% respectively. Sunlight intencity in waters had strong positive correlation to the total phenol content and reducing activity of DPPH, however, parameters of nitrate and ammonia had strong negative correlation.